Not in my backyard public sex offender registries and public notification laws - Lussier, Patrick (Canadian journal of criminology and criminal justice, 2019)
In Canada, the community risk management strategy utilized does not include a publicly available sex offender registry. While there is a non-public national sex offender registry for police investigation purposes, in recent years, there has been ongoing pressure to import American sex offender registry and notification (SORN) laws in Canada. Such pressure has been supplemented by the emergence of an increasing number of individual initiatives mimicking these policies by providing personal information through various means about individuals convicted of sex crimes. Since their inception, the American SORN laws have been the subject of much debate among scholars, policy makers, and the Victims' Rights Movement. Despite the popularity of American-style SORN laws among certain circles, policy evaluation research has not presented convincing evidence that such measures carry a crime prevention impact. In fact, American scholars have highlighted several issues, problems, and challenges that are overlooked by promoters of SORN policies in Canada. The mere presence of such policies in the U.S. should not be interpreted as an indication of good policing of sexual violence and abuse. A concerted scientific approach rather than punitive populism is much needed to tackle the issue of sexual violence and abuse in Canada